SAT0138 Cumulative Burden of Rheumatoid Arthritis Disease Severity Impacts Cardiovascular Disease Risk. (10th June 2014) - Myasoedova, E.; Chandran, A.; Ilhan, B.; Major, B.; Matteson, E.L.; Crowson, C.S.
Abstract : Background: Rheumatoid arthritis (RA) disease severity is linked to unfavorable cardiovascular disease (CVD) outcomes. Cumulative measures of RA disease burden on CVD have not been well-studied and could be used to determine the potential impact of treat-to-target strategies on CVD risk in RA. Objectives: To examine the impact of long-term cumulative burden of RA disease severity on CVD in RA. Methods: The previously validated RA medical Records-Based Index of Severity (RARBIS 1 ) and Claims-based Index of RA Severity (CIRAS 2 ) were used to estimate RA severity in an incident cohort of Olmsted County, MN, USA residents with RA who were ≥30 years old, fulfilled 1987 ACR criteria in 1988-2007, and had no history of CVD. Medical record review was used to collect data at each medical visit to calculate the RARBIS: joint surgeries, erosions, extra-articular manifestations, arthritis flares, morning stiffness, rheumatoid factor (RF) positivity, acute phase reactants and antirheumatic medications. Claims data were used to calculate the CIRAS daily during follow-up using 1 year prior data on number of inflammatory marker tests, platelet counts, chemistry panels, rheumatology visits, rehabilitation visits, assessment of RF, and Felty's syndrome. Data on CVD risk factors (i.e. hypertension, diabetes, smoking and dyslipidemia) and incident CVD (i.e. myocardial infarction, CVD death, angina, stroke, intermittent claudication, and heart failure) were also collected. Cox models with time-dependent covariates were used to assess the association of RARBIS and CIRAS with CVD, adjusting for age, sex, calendar year of RA, CVD risk factors and antirheumatic medication use. Results: The study included 525 patients with RA (mean age at RA incidence 54.6 years, 71% female). During the mean follow-up of 10.1 years, 129 patients developed CVD. The mean RARBIS and CIRAS scores at RA incidence were 2.5 (SD 1.1; min 0; max 7) and 4.5 (SD 1.9; min 0.6; max 9.5). There was no apparent association of RARBIS or CIRAS at RA incidence with CVD risk (hazard ratio [HR] 1.07 per 1 unit increase, 95% confidence interval [CI] 0.89-1.30, p=0.46 and HR 1.06, 95%CI 0.95-1.17, p=0.32). The highest RARBIS and CIRAS values in the first year were marginally associated with higher CVD risk (HR 1.12, 95%CI 0.99-1.27, p=0.08 and HR 1.16, 95%CI 1.01-1.32, p=0.03). Increase in cumulative moving average of daily CIRAS was associated with increased CVD risk (HR 1.39, 95%CI 1.13, 1.71, p=0.002). Furthermore, patients who spent more time in medium and high CIRAS tertiles were more likely to have an increased risk of CVD vs those who spent more time in the lower tertile (HR 1.09, 95%CI 0.98, 1.20 and HR 1.19, 95%CI 1.07, 1.32, respectively, per 1 year increase; p=0.004). However, the associations between cumulative measures of RARBIS and risk of CVD were not significant. Conclusions: Higher long-term burden of RA severity as expressed by cumulative moving average of daily CIRAS and cumulative amount of time in medium and high CIRAS tertiles was associated with significantly increased risk of CVD in RA suggesting accrued detrimental impact of RA severity over time. This implies that treat-to-target strategies designed to minimize cumulative disease burden could have a positive impact on the risk of CVD in RA. References: Cabral et al. Arth Rheum 2005;53:61-6. Ting et al. Arth Res Ther. 2008;10:R95 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3880